2016
DOI: 10.1002/pssb.201552571
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic insight into the pump–probe relaxation dynamics of superconductors: Model study of MgB2 relaxation within nonlinear response theory

Abstract: ReceivedHere we present a quantum-statistical formulation of relaxation dynamics of superconductors related to pump-probe (PP) spectroscopy. The method is based on the perturbation expansion of the non-equilibrium density matrix for calculation of multi-time correlation functions, and the corresponding response function. As a model for our study, the high-temperature superconductor MgB 2 has been selected. Knowledge of the electronic structure and of the corresponding Eliashberg function of electron-phonon (EP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
(144 reference statements)
0
5
0
Order By: Relevance
“…More specific arrangement of the theory toward superconductivity is available in the form of open access papers [52][53][54] in physical journals. On semiempirical level, the theory was applied to study superconductivity 48,[55][56][57][58][59][60][61][62] in anti-adiabatic state for different groups of superconductors or to study some spectral properties of superconductors, e.g. ARPES 55,56 or pump-probe spectroscopy of relaxation processes in superconductors 62 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…More specific arrangement of the theory toward superconductivity is available in the form of open access papers [52][53][54] in physical journals. On semiempirical level, the theory was applied to study superconductivity 48,[55][56][57][58][59][60][61][62] in anti-adiabatic state for different groups of superconductors or to study some spectral properties of superconductors, e.g. ARPES 55,56 or pump-probe spectroscopy of relaxation processes in superconductors 62 .…”
Section: Discussionmentioning
confidence: 99%
“…On semiempirical level, the theory was applied to study superconductivity 48,[55][56][57][58][59][60][61][62] in anti-adiabatic state for different groups of superconductors or to study some spectral properties of superconductors, e.g. ARPES 55,56 or pump-probe spectroscopy of relaxation processes in superconductors 62 . It has been shown that, no matter if EPC is strong or weak, adiabatic → anti-adiabatic state transition is the effect common for superconductors of different groups, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations